Protocol for Participatory on-Farm experiment for Aquaculture Homestead Pond - Tuy, Sinak; Freed, Sarah; Sithirith, Mak; Sean, Vichet; Sun, Vathanak; Ouk, Hak; Kong, Sovannara (WorldFish, 2023)
The Asian Mega-Deltas is one of the CGIAR’s research initiatives which aims to create resilient, inclusive and productive deltas, which maintain socio-ecological integrity, adapt to climatic and other stressors, and support human prosperity and wellbeing, by removing systemic barriers to the scaling of transformative technologies and practices at community, national and regional levels. Work Package 1 (WP1), Adapting deltaic production systems, one of AMD’s five work packages, will facilitate scaling innovation to support resilient diversified deltaic production systems and reduce environment footprints and climatic risks. At the local scale, WP1 (Adapting Deltaic Production Systems) builds networks with partners to establish learning alliances within which communities can explore new agriculture production enabled opportunities for sustainable intensification and engage with new value chains to meet burgeoning demand from within and outside delta regions. The main objective of the demonstration is: 1) To identify the potential productions for income and nutrient for rural people; 2) To introduce and demonstrate the technologies adapted climate resilience to increase productivities.